THE DETECTION OF FRAUD : HOW DO FINANCIAL STABILITY AND FINANCIAL DISTRESS AFFECT FRAUDULENT FINANCIAL REPORTS? - Nurul Hidayah Nurul; Fitria Ningrum Sayekti Fitria (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
The rise of financial statement fraud is currently the basis for research conducted. Companies often use financial statement fraud schemes. These show how important it is to check on a business' health often and take corrective measures if necessary. Falsifying financial accounts is a common practice among businesses to give the impression that everything is fine when it is not. The purpose of this study is to estimate and analyze how financial stability and financial distress impact financial statement fraud.Â The investigation will encompass all manufacturing businesses listed on the Indonesia Stock Exchange between 2020 and 2022. Based on the results of the purposive sampling method, We used Â a sample size of 35 companies Â for the study, which equates to about 105 sample data will be observed for three years, from 2020 to 2022. After that, multiple linear regression is used to analyze the data. This study contributes to the increasing body of data indicating the incidence of fraudulent accounting is not the same in times of economic boom and bust. This research shows that financial stability has not a deleterious effect on the likelihood of financial statement fraud and financial distress significantly and positively affects financial statement fraud.. The implication to the research, it is crucial for businesses to adopt preventive measures and to ascertain early on whether they are healthy or not in order to avoid making false financial statements.